2014
DOI: 10.1016/j.transci.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Acute extravascular hemolytic transfusion reaction due to anti-Kpa antibody missed by electronic crossmatch

Abstract: Acute extravascular hemolytic transfusion reaction may occur due to undetected anti-Kpa alloantibody. Various strategies for crossmatching are discussed in the context of antibodies to low incidence antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Concerning the role of immunohematological testing in detection of red cell alloantibody, Padmore et al have reported on the implication of anti-Kp a in causing an acute extravascular haemolytic reaction in a patient, where the antibody was missed by electronic cross-match [13]. Therefore, despite the nature of antibody, red cell antibody if detected in pre-transfusion testing and found to be reacting at 37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the role of immunohematological testing in detection of red cell alloantibody, Padmore et al have reported on the implication of anti-Kp a in causing an acute extravascular haemolytic reaction in a patient, where the antibody was missed by electronic cross-match [13]. Therefore, despite the nature of antibody, red cell antibody if detected in pre-transfusion testing and found to be reacting at 37…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of Kp a antigen accounts for less than 2% of individuals globally and varies from 0 to 0Á01% in Asian ancestry [1,2]. Though the original report of anti-Kp a was naturally occurring [3], the later anti-Kp a reports were identified in patients who had a prior red cell sensitizing event [4][5][6][7][8][9][10][11][12][13][14][15]. Many Gram-negative intestinal flora is known to act as primary immune stimuli for the development of naturally occurring antibodies, and several authors have shown Escherichia coli infection to stimulate antibody production against K antigen of Kell blood group system [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique cannot detect the warm, incomplete antibodies and complement. The risk of acute hemolytic transfusion reaction due to the missed antibody of low-frequency antigen has been estimated at 1 per 650,000crossmatchess using immediate spin or electronic crossmatch technology (11).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most commercially available screening kits do not contain Kp a -positive cells. Nonetheless, it is widely acknowledged that anti-Kp a antibody may cause severe HTR and HDFN [16,17,18,19,20,21,22]. Indeed, despite the infrequent occurrence, its investigation through Kp a -positive screening cell panels is undoubtedly worthy in clinical practice.…”
Section: Discussionmentioning
confidence: 99%